2022
DOI: 10.3390/polym14081521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Solutions on the Colour Stability of Nanoparticles or Fibre Reinforced PMMA

Abstract: This study aimed to evaluate the colour stability of polymethyl methacrylate (PMMA) denture base reinforced with ZrO2 nanoparticles, E-glass fibres, and TiO2 nanoparticles at various concentrations over 180-day storage in Steradent™ (STD) denture cleaner or coffee (CF). A total of 130 disc-shaped specimens were fabricated at various filler concentrations and divided into four main groups to measure the colour changes. Groups Z, T, and E consisted of PMMA reinforced with ZrO2 nanoparticles, TiO2 nanoparticles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In a previous study, it was found that adding 2.0 wt.% TiO 2 NPs to PEMA soft liners resulted in a decrease in hardness, no change in shear bond strength, and an increase in the opacity of the liner material [ 27 ]. Similar results regarding the degradation of the mechanical and color properties of the PMMA denture base with the addition of TiO 2 NPs were also reported [ 37 , 38 , 39 ]. It was found that the surface hardness of a nano-filler reinforced PMMA increased when the TiO 2 NPs concentration was increased [ 37 ].…”
Section: Discussionsupporting
confidence: 84%
“…In a previous study, it was found that adding 2.0 wt.% TiO 2 NPs to PEMA soft liners resulted in a decrease in hardness, no change in shear bond strength, and an increase in the opacity of the liner material [ 27 ]. Similar results regarding the degradation of the mechanical and color properties of the PMMA denture base with the addition of TiO 2 NPs were also reported [ 37 , 38 , 39 ]. It was found that the surface hardness of a nano-filler reinforced PMMA increased when the TiO 2 NPs concentration was increased [ 37 ].…”
Section: Discussionsupporting
confidence: 84%
“…In this study, coffee appears to have an extreme influence on the CF (coffee) change in comparison to the denture cleaner STD (Steradent)/CF. TiO2-reinforced PMMA in coffee showed the lowest color stability, while the E-glass-fiber-reinforced PMMA in STD/CF showed the highest color stability [36].…”
Section: Discussionmentioning
confidence: 94%
“…Along with thermal fluctuations, the media's chemical environment was identified to influence the properties of polymer resins [30]. In the present study, specimens were subjected to a chemical aging process by immersion in artificial saliva with a cyclic procedure of 6 h at pH = 3, interchanging with 18 h at pH = 7 for 28 days.…”
Section: Discussionmentioning
confidence: 97%
“…Another critical aspect is pointed out in some studies, which concluded that incorporating an antimicrobial drug into resin-based polymers produces color changes with clinical relevance when submitted to stainable liquids, such as coffee and wine [30][31][32]. In the case of CHX used as a mouthwash or gel, brownish staining of the teeth, mucosa, and biomaterials can cause unesthetic results [33].…”
Section: Introductionmentioning
confidence: 99%